Carmen Christi de Filipenses 2.5-11 e sua estrutura quiástica - Santos, Stefano Alves dos (2013)
The present work has as its corpus the Epistle of Paul to the Philippians, especially the Hymn of chapter two, from verses five to eleven. There are two categories: the Epistle as a literary genre and the rhetorical figure of speech that structures the whole hymn and that is called chiasm. The work consists in an attempt to analyze the Carmem Christi and its chiastic structure, seeking to show how Paul used this figure of speech in order to structure this hymn. Parallelism is the main characteristic of Hebrew poetry (and chiasm is a subtype of parallelism, that is, a parallelism inverted), although Paul has written the hymn in Greek language, he writes according to Jewish poetic model and not Greek, making use of chiasm as he structures Carmen Christi for the purpose of emphasis and memorization. Therefore, it is crucial to know this figure for the correct analysis of the hymn proposed.